Kajian Kebutuhan Luasan Terminal Penumpang Bandar Udara Pengumpan (Studi Kasus : Bandar Udara Tunggul Wulung, Cilacap) - , JOKO TRIKANGKO ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Increasing number of passengers cause queues and crowd at the passenger terminal either in the hub or spoke airport. For that to need known whether standards of passenger terminal area used in Indonesia has been in accordance with the needs and how many the needs of the passenger terminal area in accordance with standards IATA, JICA and the FAA. This research was conducted by calculating the needs of facilities terminal area by the method of IATA, JICA and the FAA based on the number of peak hours passengers derived from the number of annual passengers that have been set in SKEP. Then, conducted an analysis of existing conditions at Tunggul Wulung Airport includes: area, capacity, composition and layout of each main facilities of passenger terminal. The results of the analysis indicate broad needs of the terminal based on the main facilities is larger than the SKEP of 195.380 m2 is greater than 120 m2(25000 passengers per year) and 363.543 m2 is greater than 240 m2(50000 passengers per year). The composition of the passenger terminal Tunggul Wulung Airport is the main facilities area of 465 m2, supporting facilities covering an of 45 m2 and commercial facilities covering an area of 30 m2. Capacity of passenger terminal Tunggul Wulung Airport is 44 passengers at the peak hours so it is still able to accommodate the current number of passengers is 10 passengers at the peak hours. Development of the terminal needs to be done in 2013 because the number of passengers has reached 92 passengers at the peak hours so exceed the capacity terminal. Phase I development area of passenger terminal of Tunggul Wulung Airport is 1826.659 m2 and phase II is 2227.347 m2.